Komunikacijski model in njegova usmerjenost k razvoju kongruentne komunikacije na primeru raziskovanja skladnosti vrednostnih sporočil - Spehnjak, Marijan (visokošolska dela, 2021)
With the impact of scientific-technological civilization not just the way we communicate has changed but also whole way people live. The person, used to be the basic of communication relationships, today the focus is on technology with what the personal relationship is lost and networking towards common interestcomes to the fore. The interest of this paper is focused on the actors of each human communication % communicator/individual as a message sender,without neglecting the recipient's messages,precisely because of the new communication opportunities. Within that context, in dissertation as a sample selected group of football coaches will be explored as so called teachers which are obligated to use communication face to face in their day to day work. From communicational and theoretical point of view and with the use of philosophical reflection, especially with the philosophy of existence in which the human is their focus of interest, as is his communication, the deeper revelation of human as a communicator and analysis of his communication situation is enabled, which is dealt with by Karl Jasper and many others. In the paper, communicator is watched as a complete, complex and ontological whole being which communicates not only through technology means but with his whole being (Seneka).In order to be able to watch communicator as a complete we start from the dimensional ontology by Viktor Frankl (Frankl, 1996; 1998) and connect it with other authors. %According to Festinger's theory of internal justification (1957), Schulz von Thun's, compatibility with myself and with content of situation (2005), and Schwartzovu (1992)relationship of conflict between values, communicational comprehension disharmony can be noticed. In the work we will present, analyze and critically question possibilities, advantages and the importance of intrapersonal communication, congruent communication and communication model, in context of communication line coach-player.%With empirical search one wants to quantitative determinate interrelation of congruent messages through (self)assessment of coaches and perception of players. Values that are based on Schwartz's theory of universal content and structure of values, with new version of questionnaire %Portrait Values Questionnaire%(2001),are exploredwith the empirical search. Total sample of questionnaires is (N = 495) from which the number of coaches is (N = 122), and the number of players is (N = 373). The research was conducted during 2016. and 2017. in cooperation with Croatian football academy. In the paper we have explored and analyzed hierarchy of value messages which define the coach, with what he identifies himself, what he as a communicator/medium instructs to its environment, more specifically to his players. In the analysis of the obtained results it was looked forcompliance between (self)evaluation of coaches and perception of players by using the consistency of their responses to theoffered claims. If value messages are inconsistent with players evaluation it can lead to communication disharmony andvalue inconsistency has its source in the communicators intrapersonal aspect. It will appear in the moments when communicator sends message which is not in consistent with itsvalue habitusand in the way it is conveyed to the players.%With determination of compatibility or discrepancy of correlation relationships between value messages, congruency has set, moreover their lack of congruency. The paper identifies examples of value messages where there is compatibility, relatively examples of the discrepancy in correlation relationships between value messages. %In order for empirical and theoretical aspect of communication became more understandable we have suggested communication model which emphasizes the ontological perspective of the communication act.Because of this presented communication model itis clarified a new perspective of intrapersonal communication and the congruence of value messages.
Keywords: communication model; communication-cognitive disharmony; congruent communication; disertacije; football coaches; igralci; intrapersonal communication; intrapersonalna komunikacija; komunikacijski modeli; komunikacijsko-kognitivno neskladje; kongruentna komunikacija; nogometni trenerji; sporočila o vrednotah; universal values; univerzalne vrednote; value messages; vrednostna sporočila